1983
DOI: 10.1002/maco.19830340806
|View full text |Cite
|
Sign up to set email alerts
|

Zum Rosten des Eisens

Abstract: Es wird ein Modell vorgeschlagen, auf dessen Basis die Vielfalt der phanomenologischen Varianten des Rostens auf einige wenige Grundvorgange zuriickgefuhrt werden kann. Der erste Teilschritt der Rostbildung besteht danach in einem Durchtritt von Eisen(I1)-Ionen von der Metalloberflache in die Phasengrenzschicht, in der sie von Wassermolekiilen oder Hydroxidionen umgeben werden. Dort oder nach ihrem Abtransport in die angrenzende Elektrolytlosung werden sie durch Sauerstoff oder andere Oxydationsmittel, gegeben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Worch et al reported in 1983 [173] that GR1 is often seen on iron and steel exposed to marine environments and that chloride may also be involved catalytically in the formation of akaganeite. Akaganeite is produced only in the presence of sufficient concentrations of Cl − [107,108].…”
Section: Mechanisms Of Steel In Macmentioning
confidence: 99%
“…Worch et al reported in 1983 [173] that GR1 is often seen on iron and steel exposed to marine environments and that chloride may also be involved catalytically in the formation of akaganeite. Akaganeite is produced only in the presence of sufficient concentrations of Cl − [107,108].…”
Section: Mechanisms Of Steel In Macmentioning
confidence: 99%
“…Numerous investigations have been made (e.g., [35][36][37][38][39][40][41][42] of the principal reactions involved in anodic oxidation and corrosion of iron and steel. While of substantial value, the work has been limited in two ways.…”
Section: Chemical Mechanisms Of Iron and Steel Corrosionmentioning
confidence: 99%
“…The rust layers generally include an inner region of dense, amorphous FeOOH and some crystalline Fe304 (magnetite), and an outer loose, crystalline assemblage of a-FeOOH (goethite), ~-FeOOH (lepidocrocite), and ~-Fe203 (maghemite) (20). In some environments, other constituents are favored: for example, ~-FeOOH (akaganeite) apparently is produced only in the presence of sufficient concentrations of chloride (35).…”
Section: Chemical Mechanisms Of Iron and Steel Corrosionmentioning
confidence: 99%
“…Redox processes involving iron hydroxide layers are of particular interest in corrosion and passivity of ferrous materials [1][2][3][4][5][6][7][8] and in the charge/discharge cycles of the negative electrode in Ni-Fe battery cells [9][10][11][12]. The available literature on those reactions is concerned mostly with kinetic data resulting from different types of oxide layers in contact with iron electrodes [1][2][3][4][5][6][7][8][13][14][15][16][17][18][19]. Although the structure of these layers has been extensively investigated both in situ [20][21][22][23][24][25][26][27][28][29][30][31] and ex situ [32][33][34][35], it is still highly controversial.…”
Section: Introduction 2 Experimental Detailsmentioning
confidence: 99%